Elder’s Evaluation of Presentation of Other’s Life Histories by an Abatar of PC Soft (Asian Journal of Social Science Studies, 2024)
Background: A reminiscence therapy is effective on well-being of elders as a point of view of narrators, however it has not been clear of evaluation of elders as a point of view of listeners. Purpose: The purpose of this study was to investigate evaluation of elders who listened to others’ life histories, when an abatar of PC software narrated. Method: Participants were 14 elders in a community college. They watched two presentations of other’s life histories as a form of reminiscence therapy by an abatar of a PC software. They answered some questions about utility or significance of this method, using from 1 to 5 point, and described impression of this presentation by free description. Results: The mean score of the question “This presentation method is useful to understand the reviewer’s life” was the most high (4.29). The mean score of the question “I want to leave my upbringings like this method” was low (3.57). Categories for impression chosen by a qualitative analysis were, “Effects to view of life” “Arising positive emotion” “Evaluation for method of the presentation” “Hope to leave a legacy” and “Negative attitude to reminiscence therapy.” Conclusion: Elders evaluated that this presentation method was useful to know other’s life histories, but they did not want to leave memories like this method, though some wanted to leave legacies. The presentation affected their view of life, promoting positive emotion or hope to leave legacy. Japanese people might refrain their life histories from opening to others.